Complete genome sequence of Rhizobium leguminosarum bv. trifolii strain WSM1325, an effective microsymbiont of annual Mediterranean clovers. Issue 3 (May 2010) - Reeve, Wayne; O'Hara, Graham; Chain, Patrick; Ardley, Julie; Bräu, Lambert; Nandesena, Kemanthi; Tiwari, Ravi; Copeland, Alex; Nolan, Matt; Han, Cliff; Brettin, Thomas; Land, Miriam; et al.
Abstract Rhizobium leguminosarum bvtrifolii is a soil-inhabiting bacterium that has the capacity to be an effective nitrogen fixing microsymbiont of a diverse range of annualTrifolium (clover) species. Strain WSM1325 is an aerobic, motile, non-spore forming, Gram-negative rod isolated from root nodules collected in 1993 from the Greek Island of Serifos. WSM1325 is produced commercially in Australia as an inoculant for a broad range of annual clovers of Mediterranean origin due to its superior attributes of saprophytic competence, nitrogen fixation and acid-tolerance. Here we describe the basic features of this organism, together with the complete genome sequence, and annotation. This is the first completed genome sequence for a microsymbiont of annual clovers. We reveal that its genome size is 7, 418, 122 bp encoding 7, 232 protein-coding genes and 61 RNA-only encoding genes. This multipartite genome contains 6 distinct replicons; a chromosome of size 4, 767, 043 bp and 5 plasmids of size 828, 924 bp, 660, 973 bp, 516, 088 bp, 350, 312 bp and 294, 782 bp.